Bioinformatic Identification of a Breast‐Specific Transcript Profile. Issue 6 (2nd July 2020) - Chen, Chen; Yang, Liwen; Rivandi, Mahdi; Franken, André; Fehm, Tanja; Neubauer, Hans
Abstract : Purpose: To identify a breast‐specific transcript profile for the first time, and present an updated bioinformatics strategy for searching tissue‐specific transcripts and predicting their significance in cancer. Experimental Design: The RNA‐seq data of 49 311 transcripts in 88 human tissues from the GTEx, the Illumina Body Map, and the RIKEN FANTOM5 project are integrated to screen breast‐specific transcripts. Gene Expression Profiling Interactive Analysis, TGCA, and Kaplan–Meier Plotter are used to examine their expression in cancer tissues and values for prognosis prediction. Results: Only 96 transcripts in human genome are breast‐specific for women. Among them, ankyrin repeat domain 30A (ANKRD30A) and long intergenic non‐protein coding RNA 993 (LINC00993) are further analyzed. The two transcripts are also breast‐specific in 33 types of common female cancer and are often dysregulated in breast cancer tissues. Their expression is higher in the luminal breast cancer while significantly downregulated in triple‐negative breast cancer. Moreover, the high expression levels of ANKRD30A and LINC0993 in breast cancer tissues indicate a better prognosis of patients with breast cancer. Conclusions and Clinical Relevance: Breast‐specific transcripts in human genome are rare and poorly understood currently. The data indicate that these breast‐specific biomarkers are promising candidates for screening early cancer, assessing treatment response, monitoring recurrence, identifying metastatic tumor origin, and serving as potential targets for immunotherapy.